Pendidikan Karakter Melalui Pembelajaran Sejarah Pada Era New Normal - Ranulin Windarsari (Universitas Sebelas Maret, 2022)
Character education is an effort made by schools to shape, direct, and build the behavior of students in accordance with the values that exist in certain norms. Character is needed so that students are able to face complex future challenges. Teaching history in secondary schools has a great responsibility to shape the character of students. The Covid-19 pandemic has changed the learning implementation system from face-to-face to virtual face-to-face through online learning, Blended Learning, and Limited Face-to-face Learning to reduce the spread of the Covid-19 virus. The challenge of planting character values of students in the New Normal era learning must be adjusted to the characteristics of students and the circumstances of students so that the cultivation of character education in history learning achieves the goals to be achieved and so that students are expected to be able to answer future challenges.